Undergraduate physiotherapy students’ basic wheelchair provision knowledge: a pilot study in two universities in Colombia (2020)
Purpose: Access to an appropriate wheelchair is a human right. Only between 5–15% of people who need a wheelchair have access to one. One of the key barriers to access is the lack of appropriately trained rehabilitation professionals. The objective of this study was to evaluate basic manual wheelchair provision knowledge in final-year physiotherapy undergraduate students in two programs in Colombia. Materials and methods: Students took the International Society of Wheelchair Professionals Wheelchair Service Provision–Basic Test which was administered online and in Spanish. The minimum score to pass the test is 70%; it assesses seven domains: Assessment; Prescription; Products; Fitting; User training; Follow-up, maintenance, and repairs; and Process. Results and conclusions: One-hundred sixteen students took the test and no one passed the test. The highest median domain scores were in Assessment and Process while the lowest were in Fitting and Products. The limitations of this study include that this sample does not represent all physiotherapy programmes or students in Colombia, there may be potential errors in the Spanish translation of the outcome measure, and students encountered Internet connectivity issues during the test that may have impacted their scores. Immediate interventions are required to improve teaching and students’ learning outcomes related to basic manual wheelchair provision in these two programs. This study may serve as a foundation for future regional or national studies that assess the situation of wheelchair provision training in rehabilitation programs that will inform improvement actions. This manuscript is also available in Spanish as Supplemental Material.Implications for rehabilitation This study indicates that students’ current knowledge on basic appropriate manual wheelchair provision from two physiotherapy programs in Colombia is insufficient. Students’ knowledge does not align with the minimum guidelines recommended for wheelchair service provision by the World Health Organization. Objectively identifying the gap in knowledge in rehabilitation trainees (i.e., physiotherapy students) is a strategy to promote the inclusion of assistive technology related content in formal academic training. The need to include formal training of appropriate wheelchair provision persists and without this training, people with disabilities who require a wheelchair for mobility will continue to face barriers to full participation in society. © 2019, © 2019 The Author(s). Published by Informa UK Limited, trading as Taylor and Francis Group.